Legal Regulation of Possession in the Republic of Slovenia - Vrenčur, Renato (University of Maribor Press, 2017)
Possession is actual control over a thing. While the relationship between a possessor and a thing allows the former to use the thing, enjoy it and dispose of it, it is not important if he or she also has the right to do so. Possession represents one of fundamental components (entitlements) of ownership, which, despite the fact that it only represents actual control over a thing, nevertheless indicates certain belonging of a thing to a person who exercises actual control. Possession is not a right and therefore does not include fundamental entitlements, but it does contain the entitlement to legal protection. A possessor, who does not necessarily even have the right to possess a thing, may require protection of possession either through selfhelp or with an action. The monograph comprehensively discusses regulation of possession, and at the same time offers systematically collected and arranged recent case law in this field.